Solving the Dilemma of Ostial Stenting: A Case Series Illustrating the Flash Ostial System - Riley, Robert F.; Lombardi, Bill (Cardiology and Cardiovascular Medicine, 2017)
Percutaneous coronary interventions (PCI) of right coronary artery (RCA) aorto-ostial lesions are well-known to be associated with high restenosis rates. Positioning of the stent to include ostial coverage and allow for adequate dilation while avoiding protrusion into the aorta that could prevent future engagement of the vessel can be difficult. The Flash Ostial System is a post-dilation balloon system that enables the operator to precisely position the dilation balloon at the aorto-ostium and prevent distal migration of the balloon during inflation for optimal post-dilation. We present a case series describing use of the system.